2010
DOI: 10.1523/jneurosci.5823-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

DMob4/Phocein Regulates Synapse Formation, Axonal Transport, and Microtubule Organization

Abstract: The monopolar spindle-one-binder (Mob) family of kinase-interacting proteins regulate cell cycle and cell morphology, and their dysfunction has been linked to cancer. Models for Mob function are primarily based on studies of Mob1 and Mob2 family members in yeast. In contrast, the function of the highly conserved metazoan Phocein/Mob3 subfamily is unknown. We identified the Drosophila Phocein homolog (DMob4) as a regulator of neurite branching in a genome-wide RNA interference screen for neuronal morphology mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 62 publications
1
56
0
1
Order By: Relevance
“…CTTNBP2NL, a molecule sharing similarity with CTTNBP2, associates with the PP2A protein complex, which contains PP2A, striatins, Mob3, and FAM40A/B. Striatins are highly enriched at dendritic spines (Gaillard et al, 2006), and the Mob protein family has been shown to regulate synapse formation in Drosophila (Schulte et al, 2010). FAM40A and FAM40B have recently been shown to modulate the actin cytoskeleton (Bai et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…CTTNBP2NL, a molecule sharing similarity with CTTNBP2, associates with the PP2A protein complex, which contains PP2A, striatins, Mob3, and FAM40A/B. Striatins are highly enriched at dendritic spines (Gaillard et al, 2006), and the Mob protein family has been shown to regulate synapse formation in Drosophila (Schulte et al, 2010). FAM40A and FAM40B have recently been shown to modulate the actin cytoskeleton (Bai et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that the rightward-asymmetric pathway may be related to a rightward functional lateralization of auditory spatial attention and working memory whereas the leftward-asymmetric pathway may be related to leftward functional lateralization for language, but they did not test this assumption on a behavioral level. More direct evidence comes from a combined diffusion tensor imaging tractography and functional magnetic resonance imaging study in alcoholics and healthy controls (Schulte et al, 2010) were it was observed that white matter fiber degradation in the Corpus Callosum due to alcoholism leads to an attenuated pattern of functional visuo-motor asymmetries. While these studies are only a first step, they nevertheless show that, parallel to the work that has been conducted in birds, it may indeed be a promising approach to further investigate the role of structural white matter asymmetries in the human brain in order to reveal the underlying neurophysiological processes of human functional hemispheric asymmetries.…”
Section: Connections Matter: the Role Of White Matter Tracts In Latermentioning
confidence: 99%
“…These candidates could be potentially involved in the development of neural networks specific for sperm competition and/or they could function at the time of sperm competition. Given that knockdown of at least some of these neural genes is lethal or affects behaviors unrelated to sperm competition (e.g., locomotion behaviors that could affect courtship or mating) (Loughney et al 1989;Lloyd et al 2000;Schulte et al 2010), we chose to test a specific hypothesis: that neural genes might influence sperm competition through neurons that innervate the female reproductive tract. This approach likely underestimates the extent of contribution of these genes that we found, but is a simple, initial, and direct test of function.…”
mentioning
confidence: 99%